Performance evaluation of a real-time pseudodynamic test system. - Rae-Young Jung (Earthquake engineering & structural dynamics.)
This paper presents a detailed analysis of a real-time pseudodynamic test system using a system transfer function. The analysis considers the actuator control scheme, the dynamics of the actuator, test structure, and actuator reaction frame, the influence of actuator time delay on response computation, and methods to compensate for the time-lag errors. It has been observed that the system can achieve an excellent performance with optimum control gains. The two error-compensation methods presented here are also proven to be effective. Further, it has been demonstrated that the adverse effect of the inertia force developed by the test structure can be corrected for during a real-time test, and that the influence of the reaction frame flexibility is small when the frame is reasonably massive and stiff as compared to the test structure.